2022
DOI: 10.1038/s41598-022-04861-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage EK99P-1 alleviates enterotoxigenic Escherichia coli K99-induced barrier dysfunction and inflammation

Abstract: Bacteriophages, simply phages, have long been used as a potential alternative to antibiotics for livestock due to their ability to specifically kill enterotoxigenic Escherichia coli (ETEC), which is a major cause of diarrhea in piglets. However, the control of ETEC infection by phages within intestinal epithelial cells, and their relationship with host immune responses, remain poorly understood. In this study, we evaluated the effect of phage EK99P-1 against ETEC K99-infected porcine intestinal epithelial cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Enterotoxigenic Escherichia coli (ETEC) is one of the main causes of diarrhea in farm animals, including piglets, calves, and lambs [ 1 ], and infections by ETEC in animal husbandry and aquaculture result in severe economic losses due to high animal morbidity and mortality [ 2 ]. Generally, ETEC in an exogenous environment enters animals orally and is subsequently recognized by specific receptors in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Enterotoxigenic Escherichia coli (ETEC) is one of the main causes of diarrhea in farm animals, including piglets, calves, and lambs [ 1 ], and infections by ETEC in animal husbandry and aquaculture result in severe economic losses due to high animal morbidity and mortality [ 2 ]. Generally, ETEC in an exogenous environment enters animals orally and is subsequently recognized by specific receptors in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Under the same pH as that of the piglet intestine, successful indicators were obtained: the microencapsulated FJ1 decreased EC43 load in 3.9 Log CFU cm −2 (> 99.9%), also 6 h after phage administration (Figure 3 ). Phage effectiveness in decreasing bacterial contamination in intestinal cell lines was previously observed by Mirzaei et al [ 36 ] in HT-29 and Caco-2, with reductions of 1.0 to 4.0 Log CFU mL −1 of ESBL E. coli strains for 8 h. More recently, Kim et al [ 37 ], reported that the phage EK99P-1 was able to alleviate ETEC K99-induced barrier dysfunction and inflammatory response of IPEC-J2 cultured cells. In this study, the protective effect, that FJ1 seems to have on EC43-infected cells (at least 16 h after phage administration), was observed microscopically, showing an apparent delay in cell damage.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, MJM60396 showed strong antibacterial activity against many enteric pathogens ( Table S2 ). These enteric pathogens induce intestinal toxins and cause diarrhea, and destroy the intestinal barrier by causing loss of tight junction proteins such as ZO-1 and occludin [ 47 ]. MJM60396 showed an antibacterial effect on enteric pathogens, thus protecting the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%